Determinant Model Of Early Marriage On The Promotion Of Reproductive Health In Adolescents In Mandala Village - Dian Permatasari; Emdat Suprayitno; Cory Nelia Damayanti; Dian Ika Puspitasari (Journal of Applied Nursing and Health, 2022)
Background: Early marriage is a problem at the national level and in East Java because the number is still high and continues to grow, and the impact poses a health risk to adolescents. Sumenep Regency is a district in Madura that has a high rate of early marriage and is ranked second from East Java, and Mandala Village, Rubaru sub-district, is the place with the most land for early marriage rates Methods: This research method is a survey with a cross-sectional design. The sample of this research is 80 married teenagers in Mandala Village, for the data collection tool uses a questionnaire, and the sample collection technique is multistage proportional random sampling and then analyzed using univariate, bivariate, and multivariate methods. Then a model is created Results: Based on the results of the calculation of Nagekerke R Square on the dominant variable, the value of r2 = 0.135, which means that respondents who promote adolescent reproductive health can be affected by knowledge of 5.749 times greater than respondents who promote adolescent reproductive health, with a 13.5% chance of being unaffected. Conclusion: Based on the results of the research and discussion that have been described in the previous chapter, it can be concluded that several vital things in this research are as follows, There is an influence of knowledge, attitude, the effect of Parenting, and culture on efforts to promote adolescent reproductive health in Mandala Village in 2022.